2020
DOI: 10.1101/2020.05.29.122812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gray and white matter morphology in substance use disorders: A neuroimaging systematic review and meta-analysis

Abstract: Substance use disorders (SUDs) are characterized by a compulsion to seek and consume one or more substances of abuse, with a perceived loss of control and negative emotional state. Repeated use of a substance results in synaptic and morphological changes, secondary to toxicity and SUD pathology in the dopamine striato-thalamo-cortical and limbic pathways. These neuroadaptations seem to vary between studies, which could be related to divergent effects of substances, consumption severity or other unknown factors… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 101 publications
0
16
2
Order By: Relevance
“…Finally, it should be noted that the results of our analysis are not consistent with those of another recent meta-analysis 26 , where a pattern of convergent WM volumetric alterations in AUD in the corticospinal tract and anterior thalamic radiation has been identified. However, this meta-analysis was not explicitly designed to investigate WM alterations in AUD but reported respective findings as a part of a subanalysis in a broader context based on four studies only.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Finally, it should be noted that the results of our analysis are not consistent with those of another recent meta-analysis 26 , where a pattern of convergent WM volumetric alterations in AUD in the corticospinal tract and anterior thalamic radiation has been identified. However, this meta-analysis was not explicitly designed to investigate WM alterations in AUD but reported respective findings as a part of a subanalysis in a broader context based on four studies only.…”
Section: Discussioncontrasting
confidence: 99%
“…This is possible because the ALE method itself tests directionally independent since it is not based on effect sizes 28 , which is particularly useful in the context of clinical samples, where the effects may vary over the course of the disorder (e.g. as a function of the duration of abstinence or changes in the proportion of grey to white matter) 23,26 . A close inspection of the contributing foci revealed that the ALE convergence clusters identified in our meta-analysis are largely based on studies that report a WM reduction in AUD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, studies using structural imaging method found that grey matter deficits in subjects with SUDs are not restricted to regions implicated in the brain reward system (e.g. striatum and vmPFC/mOFC), and are also frequently observed in the anterior insula, thalamus, ACC and the amygdala 18-21 . Finally, in functional brain connectivity studies (both task-based and resting-state modalities), researchers found impaired connectivity between brain regions of the reward system in individuals with SUDs 22 , with possible alterations in other brain networks such as the frontoparietal and the default-mode networks 23-25 .…”
Section: Introductionmentioning
confidence: 54%
“…. In an opposite direction but still common to drug-addicted individuals (i.e., spanning different drug classes), volumetric increases have been reported for the dorsal striatum (15) that regulates habit formation (16,17), potentially related to its dopaminergically-mediated role in cue sensitivity and craving (18).…”
Section: Introductionmentioning
confidence: 99%